Hyalella cenotensis, a new species of Hyalellidae (Crustacea: Amphipoda) from the Yucatán Peninsula, Mexico - Marrón-Becerra, Aurora; Hermoso-Salazar, Margarita; Solís-Weiss, Vivianne (Zootaxa, 2014)
In this study the first blind species of Hyalella for Mexico is described; it is the second in the genus to be recorded there. The new species is closer to the eyeless species: H. anophthalma Ruffo, 1957, H. muerta Baldinger, Shepard & Threloff, 2000, H. caeca Pereira, 1989, H. spelaea Bueno & Cardoso, 2011 in Cardoso et al. 2011, H. imbya Rodrigues & Bueno, 2012 in Rodrigues et al. 2012, but with no curved seta at the inner ramus of uropod 1, antennae 1 shorter than antennae 2, no apical setae on the telson and a characteristic dorsoposterior carina and three pappose setae on the inner plate of maxilla 1. The morphological intraspecific variations that can be found in this genus are discussed.